Numerical Modeling of Sinabung Volcano Magma Chamber Based on the GPS Data in 2012-2013 Using Very Fast Simulated Annealing (VFSA) - Ratih Kumalasari; Wahyu Srigutomo; Irwan Meilano; Hendra Gunawan (Computational And Experimental Research In Materials And Renewable Energy, 2022)
GPS data of Sinabung Volcano during year 2012 to 2013 has been processed using Gamit 10.5 then we correct the data from global and local noise to get surface paramaters of Sinabung Volcano. After we get surface parameter we applied Mc Tique model with very fast simulated annealing (VFSA) Inversion Scheme. From the inversioan we concluded that the position of magma chamber divide in 3 period, on 1st period the magma chamber is on ± 27 km, on 2nd period is on ± 16 km and the 3th period is on ± 0.5km below Sinabung Valcono. That result showed that the magma migrated from the deep into shallow part and indicated that Sinabung Volcano is on active status. Keywords: Pressure source, VFSA, McTique Model, Sinabung.